DIGITALAGE: CREATIVITY VS. CREATION - Urazova, S.L. (Vestnik Rossiĭskogo universiteta druzhby narodov. Serii͡a︡ Literaturovedenie, zhurnalistika, 2017)
The article substantiates the semantic differences between the concepts “creativity” and “creation” (from the Latin cretio - creation). These terms largely determine the development of the Information society, the digital economy, where the need for implementation of innovative projects correlates with the leading signs - originality, novelty, efficiency, interactivity, productivity, because it is necessary for civilizational advancement. For the media industry, which is residing the significant reforms at the digital age, these concepts are not less important.These terms are opposed to primitive patterns and stereotypes at the production of media. These terms also relate to the language’s opposition - “craft - creation”, which the understanding of the semantic values produces the relevant competencies among producers of media products. The article reveals the contradictions that are raised as a result of choice in favor to craftsmanship, justifies the influence of stereotypes on the modern media market.